Physicians’ perspectives on the use of Telemedicine in Germany : in the healthcare areas of diabetology, pediatrics, cardiology, neurology, and psychiatry - Grießer, Marco (2022)
Telemedicine is nowadays an instrument to enhance the conventional patient-to-doctor relationship. It can appear in many variations ranging from Covid-19 boosted video consultations to device-related monitoring of patient data by the means of telemedicine. Thus, this master thesis aims to show how different physicians apply telemedicine, the advantages, disadvantages, and challenges of telemedicine in 2021 and how Covid-19 has influenced the use of telemedicine in Germany. The scope of this study is limited to the areas of diabetes, pediatrics & diabetes, cardiology, neurology, and psychiatry & psychology. Therefore, the results of five in-depth interviews with telemedicine experts in combination with an extensive literature review show that telemedicine can compensate partially the supply shortage of skilled specialized doctors in hospitals and practices. This compensation of skilled specialized doctors can be achieved by transferring the skill set from doctors to nurses to free up time for the doctors. Also, it has been found that one of the main application areas for telemedicine are online video consultation services with a prior personal data exchange. Additionally, it can be verified that Covid-19 has had a positive effect on the acceptance of telemedicine in Germany, but no effect on the numbers of treated patients. Telemedicine cannot replace the personal face-to-face contact with doctors. However, it can help to increase the medical service in rural areas with limited specialists.